A multivariate model of perceived quality in a developing country - Chowdhury, M. Humayun Kabir; Andaleeb, Syed Saad (© 2007 Published by Taylor & Francis Online, 2016)
This article was published in the Journal of International Consumer Marketing [© 2007 Published by Taylor & Francis Online] and the definite version is available at: http://doi.org/10.1300/J046v19n04_03 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1300/J046v19n04_03